PENGARUH LATIHAN MENGGUNAKAN BOLA TENIS TERHADAP KECEPATAN REAKSI DAN KONSENTRASI KIPER FUTSAL UNESA - Wicaksono, Satrio; Kusuma, I Dewa Made Aryananda Wijaya (Universitas Negeri Surabaya, 2020)
Goalkeepers have a very big role in the game of futsal. The futsal attack and defense game starts from the goal keeper. A futsal goalkeeper must have good concentration and speed to play futsal. According to observations made by researchers, the obstacles that exist in the goalkeeper are the ability to react speed and concentration to catch the ball due to the lack of variation in training methods. Therefore, with the practice of using a tennis ball, a goalkeeper is expected to be able to practice skills, especially reaction speed and concentration in catching the ball well, which can support the quality of a futsal goalkeeper. The purpose of this study was to determine whether there is an effect of training using a tennis ball on the reaction speed and concentration of futsal goalkeeper Unesa. This research is an experimental study using the One-Group Pretest-Posttest design. The population in this study were all male futsal goalkeepers Unesa, totaling 10 goalkeepers. The technique used to take samples is saturated sampling technique. Data analysis in this study used the normality test, homegeneity test, and test. Based on the results of the data analysis carried out, it was stated that there was a less significant increase from training using tennis balls on the reaction speed and concentration of the Unesa futsal goalkeeper as evidenced by a significance value of 0.011 <0.05 and 0.000 <0.05.